An Analysis of Tenth Grade Students’ Reading Comprehension Ability in Procedure Texts - Zulkarnain Aimet; Yessy Marzona; Sherly Franchisca (JURNAL ARMADA PENDIDIKAN, 2025)
Reading skills are one of the basic skills that students must know. The researcher found problems for students in learning to read texts, especially learning to read in procedural texts. There are some students who are less able to read the text, through this problem the researcher tried to evaluate students' reading skills by reading procedural texts in class X of SMA Ekasakti Padang. Many problems were found during the observation process, including: students still have difficulty in reading procedural texts. Students cannot develop their ideas in reading procedural texts, should not have enough vocabulary, and also cannot read the correct sentences, students are lacking in pronouncing their words and vocabulary. The purpose of this study was to determine the reading comprehension of procedural texts. This research method was descriptive qualitative. hasil penilaian tes kemampuan membaca, diketahui bahwa kemampuan siswa dalam skill Judul sang tinggi (52,9), kemampuan siswa dalam Tujuan tinggi (29,4%), kemampuan siswa dalam Bahan dan peralatan tinggi (35,2%), kemampuan siswa dalam Langkah-Langkah Tinggi (17,6%). Melalui hasil penelitian tersebut, peneliti menyimpulkan bahwa skor pemahaman siswa adalah 41,47. Angka ini menunjukkan bahwa kemampuan membaca siswa dalam teks prosedural adalah tinggi.